Karakteristik Arang Kulit Durian Dan Daun Jenggelan Untuk Pembuatan Tinta Organik - Ramadhani, Devi Rezky; ., Masthura; Husnah, Miftahul (Rekayasa Material, Manufaktur dan Energi, 2024)
Printing inks contain dyes, adhesives, lubricants, plastics, surfactants and other substances. Chemical-based inks have carcinogenic, toxic, and corrosive properties that cause breathing difficulties and dizziness in humans when the substance is vaporized and inhaled, disorders of the brain, liver, and nervous system if inhaled for a long time. So an organic ink innovation is needed. This study aims (i) to determine whether durian peel charcoal and janggelan leaves can be used as a basic material for making organic ink. (ii) To determine the characteristics of organic ink made from durian skin and janggelan leaves. (iii) To determine the optimum composition of durian skin charcoal and janggelan leaves. The tests carried out are density, viscosity, surface tension and Fourier Transform Infrared (FTIR). The results obtained show that the organic ink that can be used is with a sample composition of 5 grams of durian skin charcoal, 1.5 grams of janggelan leaf extract, 96% alcohol 15 ml and distilled water 20 ml. With ink density value of 0.92 gr/cm3, viscosity value of 3.88 Cp, surface tension value of 45.802 dyne/cm. The functional groups of organic ink that have been studied are OH, CO, C=O, C ≅ C.